Ethnoscience study to convert kerinci community knowledge in the processing of kawa drinks - Haryanto, Toni; Kencanawati, Indah (Biosfer: Jurnal Pendidikan Biologi, 2023)
The district's traditional drink, kawa drink, made from dried coffee leaves, is used by the Kerinci people. The primary purpose of this investigation is to use ethnoscientific research to turn common knowledge about the techniques used in processing kawa drinks into scientific knowledge. This study employs a qualitative, ethnoscientific phenomenological methodology that includes observation, which involves learning where to gather the coffee leaves that will be used to make kawa drinks in the step one. The finding out how to turn coffee leaves into kawa drinks was the second step of the interview. The third step involves documenting several steps in the processing of coffee leaves into kawa drinks and the data must then be subjected to a descriptive qualitative analysis as the final step. The Miles-Huberman approach for data analysis includes data reduction, data presentation, conclusion-drawing, and verification. The study's results show that while the process of transforming kawa drinks into traditional drinks is a local tradition that has developed over the years, the tradition of drinking kawa has not changed since the transformation of local knowledge. The six steps make up the process of converting coffee leaves into kawa drinks: leaves collection, drying, smoke of kawa leaves, packaging, dissolving, and serving drinks. The tradition of making and consuming kawa drinks in Ujung Pasir Kerinci Village has the potential to serve as a source of community knowledge to convert of tradition into scientific science.